2020
DOI: 10.1111/dmcn.14607
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic cervical spinal stenosis in spastic cerebral palsy

Abstract: Aim To describe the prevalence of symptomatic cervical spinal stenosis (CSS) in spastic cerebral palsy (CP) and associated characteristics. Method This cross‐sectional study of adults (>18y) with CP (2006–2016) at a single institution compared the patient characteristics (demographics, comorbidities, surgical history, medications, Gross Motor Function Classification System [GMFCS] level, and CP type) of patients with and without CSS. Results Of 424 patients (mean age 33y 4mo, SD 13y 6mo, range 18–78y; 225 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…CP is associated with a higher risk of cervical myelopathy than focal cervical dystonia, suggesting that cervical dystonia is not the only risk factor for myelopathy 27 . Supporting this point, a recent study found that 7.5% of adults with spastic CP had symptomatic cervical spinal stenosis 28 . Thus, some orthopedists recommend screening all adults with CP over age 50 years for cervical spinal stenosis with cervical spine X‐rays 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CP is associated with a higher risk of cervical myelopathy than focal cervical dystonia, suggesting that cervical dystonia is not the only risk factor for myelopathy 27 . Supporting this point, a recent study found that 7.5% of adults with spastic CP had symptomatic cervical spinal stenosis 28 . Thus, some orthopedists recommend screening all adults with CP over age 50 years for cervical spinal stenosis with cervical spine X‐rays 29 .…”
Section: Resultsmentioning
confidence: 99%
“…27 Supporting this point, a recent study found that 7.5% of adults with spastic CP had symptomatic cervical spinal stenosis. 28 Thus, some orthopedists recommend screening all adults with CP over age 50 years for cervical spinal stenosis with cervical spine X-rays. 29 Importantly, neurologic screening recommendations for spondylotic myelopathy in this neurologically complex population are lacking, which is problematic given that spondylotic myelopathy can often yield subtle symptoms even in otherwise healthy individuals.…”
Section: Myelopathymentioning
confidence: 99%
“…However, there are several diagnoses that are relatively common in adults and uncommon in children. Table 1 illustrates findings in the history and physical examination that could be possible indicators of pain in adults (1,15,(22)(23)(24). The diagnoses associated with these findings should also be considered in the evaluation of behavior change in adults with childhood-onset disabilities and communication impairment.…”
Section: Special Considerations For Adults With Childhood-onset Disabilities and Communication Difficultiesmentioning
confidence: 99%
“…Because of advancements in medicine, people with childhood-onset disabilities commonly live into adulthood (1,2). One of the most common childhood-onset disabilities is cerebral palsy (CP), a group of movement disorders caused by a disturbance to the fetal or infant brain (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…For the patient with cerebral palsy (CP), this challenge is compounded by preexisting abnormal neurological impairments and possibly also by communication impairment. Hung et al 1 found a prevalence of 7.5% of symptomatic CSS in a series of adults with CP. Two issues are critical in this complex topic.…”
mentioning
confidence: 96%